The obstetric outcome among primiparity and multiparity on epidural analgesia in Hospital Universiti Sains Malaysia - Mansor, Halimatun (2010)
Objective To determine the obstetric outcomes of primiparity and multiparity who received epidural analgesia during labour in Hospital Universiti Sains Malaysia (HUSM). Methodology A cross sectional study involving 248 pregnant mothers, primiparity and multiparity, who received epidural analgesia (study group) and another 251 will received other methods of analgesia during intrapartum (control group) in HUSM from January 2007 to December 2008. All patient on epidural analgesia will be taken as a participant after consent is taken. The epidural analgesia will be perfonned by the anesthetic team. The patient will receive epidural analgesia (Ropivacaine 0.125% and fentanyl 0.2mg/ ml) once they are in labour. The duration of first stage of labour will be taken at the time of ARM after epidural analgesia was given till fully dilatation of cervix. Patient with the cervical dilatation of 3cm and 4 em will be recruited into the study to avoid bias. The duration of second stage of labour will be taken from the time of active pushing at full dilatation of cervix until the fetus was expelled out. The duration of third stage of labour will be taken from the delivery of fetus until the placenta is delivered. All the duration taken will be calculated in minutes. The mode of delivery and the used of oxytocin augmentation will be evaluated and analyzed in both groups. The neonatal outcomes reviewed were Apgar Score at one minute and five minutes, the requirement of naloxone to the baby and NICU admissions. The maternal complications were elicited from the time of epidural analgesia given till the next 24 hours. Results There were 499 patients in this study population which was well distributed consisting of 124(24.8%) patient for primiparity and 124(24.8%) multiparity on epidural and 124(24.8%) primiparity and 127(25.5%) multiparity for control group which used other method of analgesia such as IM Pethidine or Entonox. There were significant different in mean duration first stage of labour between primiparity and multiparity of both epidural and non epidural groups(p < 0.001). The mean duration of first stage of labour in PE was 424.72 ± 165.70 which was longer than ME group with mean duration of 344.61 ± 142.14 minutes. The control group PC and MC showed shorter mean duration of first stage of labour which were 327.22 ± 175.35 and 263.56 ± 139.75 minutes respectively. Comparing between epidural and non epidural group, there was significant longer in the mean duration of first stage of labour with p < 0.001 which were 384.67 ± 159.20 versus 295.01 ± 161.21 minutes. There was also significant association between epidural and parity , the epidural group and parity have a longer duration first stage of labour with adjusted means 375.98 (95% CI 356.47, 395.49) and 304.08 (95% CI 284.69, 323.48) minutes comparing to each group with p= 0.00 1. However, there was no significant interaction in mean duration first stage of labour between epidural and parity . In second stage of labour the PE group showed significantly longer mean duration of second stage of labour than ME ( 21.45 ± 22.31 versus 13.82 ± 14.03) minutes. Similarly, the duration of second stage of labour was prolonged in PC as compared to MC. There was no significant different in mean second stage of labour between epidural group and controlled group with ( P == 0.4 70) and no significant association in mean second stage of labour in epidural with parity, C P =0.451 ). There was significant association between primiparity and multiparity group, with adjusted mean 21.82 minutes and 14.68 with p < 0.001. However, there was no significant interaction between the use of analgesia and parity, p = 0.759. There was no significant different in mean duration third stage of labour. In mode of delivery, LSCS was highest among the PE ( 30.6%) followed by ME ( 20.2% ), PC ( 12. 1 %) and MC ( 7.1% ). LSCS was significantly higher in epidural group compared to controlled group , ( p < 0.001 ). There were no significant different in number of ID in both primiparity and multiparity groups as well as in epidural and non-epidural group. The incidence of Spontaneous Onset of Labour (SPL) was significantly low in PE and ME ( 60.5% and 66.5%) compared to controlled groups ( 82.3% and 93.7% ). There was significantly low incidence of SPL in epidural group than controlled groups ( 63 .7% versus 88.1 %), p < 0.001. SPL is likely to have SVD compared to induced labour ( 82.8% versus 64%). The incidence of LSCS followed by SPL and induced labour was 12.4% versus 33.3% .. In multivariate analysis there was significant association between spontaneous vaginal delivery and usage of epidural (p <0.001). Patient who had spontaneous onset of labour less likely to go for cesarean section with OR= 0.37 and Epidural usage has 2.5 times risk for cesarean section. There was no significant interaction between spontaneous onset of labour and used of epidural p== 0.502.